Russian dacha from Petersburg to Harbin: Stylistics and semantics - Ivanova, Alina (project baikal, 2023)
The article is devoted to little-studied aspects of the Russian countryside culture. New materials from the archives of the Russian State Historical Archive are introduced into the scholarly discourse. The author considers different trends in dacha architecture on the basis of projects for the suburbs of St. Petersburg.